Efficacy of Tacrolimus plus Narrow Band Ultraviolet B Phototherapy versus Narrow Band Ultraviolet B Phototherapy alone in the Treatment of Vitiligo - Rehman, Somaiya; Azam Khan, Farooq; Zahoor, Hina; Taqweem, Nafila; Mahmood Noor, Sahibzada; Naheed, Nuzhat (Journal of Neonatal Surgery, 2025)
Introduction: Vitiligo Is Considered As One Of The Most Prevalent Depigmentary Condition Affecting 3-4 % Of Indian Population. In Pakistan The Reported Prevalence Is 4.4- 7.5 %. Vitiligo Is Divided Into Generalized Or Non-Segmental Vitiligo Characterized By White Patches, Therapies Include Topical Corticosteroids, Topical Immunomodulators, Calcium Modulators, Phototherapy, Surgery, Laser, Combination Therapies, Depigmentation Of Normally Pigmented Skin And Adjunctive Therapies Like Sunscreen And Camouflage Are Used. Objective: To Compare The Efficacy Of Tacrolimus Plus Narrow Band Ultraviolet B Phototherapy Versus Narrow Band Ultraviolet B Phototherapy Alone In The Treatment Of Vitiligo. Methodology: The Current Randomized Controlled Trial Was Carried Out At The Department Of Dermatology, Lady Reading Hospital, Peshawar For A Period Of Six Months From January 2023 To June 2023. Total Sample Size Was 94 Patients I.E 47 In Each Group. All Patients Were Randomly Allocated Into Two Groups By Lottery Method. Patients In Group A Were Subjected To Combined Treatment I.E; Narrow-Band Ultraviolet B Three Times A Week Plus Topical Tacrolimus 0.1% Once Daily Application While Patients In Group B Were Subjected To Narrow-Band Ultraviolet B Three Times A Week Alone For Three Months. Assessments At Baseline And Repigmentation Of Vitiligo Areas On Follow Up After 12 Weeks Was Recorded. Data Were Analyzed In Spss Version 24 Result: A Total Of 94 Patients Were Observed, Which Were Divided In Two Equal Groups. Male To Female Ratio Was 0.59:1. Average Age Was 28.59 Years+ 8.86sd With Range 15-51 Years. Efficacy Wise Distribution Was Significant With P-Value = 0.022. Group Group A Showed 41(87.2%) Efficacy While Non-Effective In 6(12.8%) Patients. Similarly Group B Showed 32(68.1%) Efficacy While Non Effective In 15(31.9%) Patients. The Combination Therapy Have Greater Efficacy Than Monotherapy. Conclusion: Combination Therapy Is More Effective Than Monotherapy In The Treatment Of Vitiligo. ..